International Relations and Asia's Southern Tier ASEAN, Australia, and India (Asan-Palgrave Macmillan Series, 2018)
This book, part of a series, seeks to re-conceptualize Asian geographies; rather than a static East Asia core, this volume analyzes Asia's southern fringe, as symbolized in the trading group ASEAN and its role in Asia's evolving international relations. The contributors include many leading experts in the field, ensuring that this book will be the go-to text for students, scholars, and civil society decision makers exploring Asia's contemporary political spectrum in real time.